Using hike-along ethnographies to explore women's leisure experiences of Munro bagging. Issue 5 (2nd September 2020) - Brown, David M; Wilson, Sharon; Mordue, Tom
ABSTRACT: This methodological study analyses the merits of adopting an ambulatory 'hike-along' approach to explore the mobile experiences of women during serious leisure pursuits such as Munro-bagging – climbing Scotland's 3, 000 feet high mountains. By walking with participants as they ascended their chosen routes, rather than relying on sedentary, post-hoc interviews, we were able to observe the transient, shifting natures of their pastime, the embodied relationships between self and landscape, previously overlooked moments of 'in-between-ness', liminalities between mobility and immobility, and the ways in which women live their experiences into being, intertwining their self-concepts with emerging understandings of their environment. The 'nowness' of our methodology captured the inseparability of actor, (inter)action, self, movement, and temporospatial and sociocultural contexts. Moreover, the inherent mobility of our approach brought a congruence with the subject matter, participants, settings and phenomena of study, which helped to separate women's adventure identities from the androcentricity permeating the canonical literature on walking. We therefore recommend broader adoption of 'hike-alongs' within similar ethnographic studies of serious leisure.